Baş-boyun mukozal malign melanomlu üç olgunun sunumu - (:unkn) unknown (My University, 2006)
Mukozal malign melanomlar otolaringolojide seyrek görülen kötü prognozlu tümörlerdir. Tüm mukozal malign melanomların %0.5-2’si baş boyun bölgesinde yerleşmiştir. Baş boyun bölgesinde en sık nazal kaviteyi, daha az olarak da oral kaviteyi tutarlar. Genel olarak şüphelenilen her lezyondan biyopsi alınmalı ve malignite açısından araştırılmalıdır. Bu tümörlerin güvenilir tanısında immünhistokimyasal metodlar kullanılır. Erken tanı ve yeterli cerrahi eksizyon agresif seyirli ve kötü prognozlu bu tümörleri kontrol etmek için gereklidir. Mukozal malign melanomların primer tedavi yöntemi cerrahidir. Cerrahi tedavinin yetersiz kaldığı durumlarda radyoterapi uygulanabilir fakat radyoterapi yalnız başına hastalığın lokal kontrolünde etkili olsa da hastalığı tamamen ortadan kaldırmada yetersizdir. Kemoterapi tek başına etkisizdir, ancak metastaz yapmış ileri evre olgularda cerrahi ve radyoterapi ile birlikte kullanılır. İmmünoterapi son yıllarda tedavide kullanılmaya başlamıştır. Bu yazıda 1989 ile 2004 tarihleri arasında Marmara Üniversitesi Hastanesi’nde mukozal malign melanom nedeniyle takip ve tedavi edilen üç olgu sunuldu. Hastaların semptomları, tanıları, tedavileri ve prognozları değerlendirildi. Olgularımızdaki mukozal malign melanomlar bir hastada nazal bölgede, bir hastada orta kulakta ve diğer hastada nazofarenkste yerleşmişti. Olguların tamamı tüm tedavilerine rağmen 5 yıl içinde kaybedildi.

Primary malignant mucosal melanoma of the head and neck is a rare and usually lethal disease, accounting for only 0.5-2% of all malignant melanomas. Of lesions arising in head and neck, the most frequent location is the nasal cavity followed by the oral mucosa. In general, suspicious lesions should be biopsied and examined for possible malignancy. Immunohistochemistry has added ability to make a confident diagnosis of malignant mucosal melanoma in the head and neck. Despite the rarity of mucosal melanomas, their agressive behavior and poor prognosis warrants investigation at an early stage. Surgical resection is the primary treatment modality for mucosal melanomas. Radiation therapy alone may be effective in controlling local tumor spreading, but it is not effective in completely eradicating the tumor. Chemotherapy as a sole treatment modality is ineffective but it is used in distant metastatic disease combined with surgery and radiation therapy. Immunotherapy has been recently used to treat mucosal melanomas. We reviewed three patients treated at Marmara University Hospital for mucosal malignant melanoma of the head and neck between 1989 and 2004. We analyzed clinical presentation, diagnosis, treatment modality and survival of patients. Among our patients, one melanoma was in the nasal cavity, one was in the middle ear and one was in the nasopharynx. Despite treatment all of the patients died in 5 years.
Mucosal melanoma of the head and neck: report of three cases
Keywords: Tıbbi Araştırmalar Deneysel; Onkoloji